ANALISIS SENSITIVITAS USAHA PENGOLAHAN COKELAT BERBASIS IKM (INDUSTRI KECIL MENENGAH) DI KOTA PALU SULAWESI TENGAH - Marliyah; Haeruddin; Muhamad; Mukhlis (Jurnal Penelitian Pendidikan IPA, 2025)
Agroindustry, as a vital subsystem in agribusiness, has great potential to boost economic growth through significant market share and added value. Most of this sector is dominated by small and medium enterprises (SMEs). Business sustainability can be assessed by its response to changes, such as raw material prices and production declines due to falling demand. This study aims to evaluate business feasibility and sensitivity to changes in raw material prices and production in the chocolate industry. This quantitative descriptive study was conducted in four chocolate processing SMEs in Palu, Central Sulawesi, from September to November 2023 with respondents selected purposively, namely 4 leaders of chocolate SMEs. The analysis used included financial feasibility and sensitivity analysis. The results show that the financial feasibility of chocolate SMIs in Palu, both for secondary and tertiary products, is feasible based on the NPV, IRR, and B/C criteria, with Ema Cokelat SMI being the best. The fastest return on investment was also achieved by Ema Cokelat SMI, which was 2 years and 4 days. In the sensitivity analysis, secondary and tertiary products with an interest rate of 18% showed that the Chocolate Home Industry and Rapoviaka Simple SME were sensitive to a 30% decrease in production and an increase in raw material prices. Meanwhile, Ema Cokelat SME was not sensitive to these two changes, and Sakaya Cokelat SME was sensitive to a decrease in production but not to an increase in raw material costs.